Assessing the parental SES gradient in young Britons’ partnership expectations, attitudes and its potential mediators - Palumbo, Lydia; Berrington, Ann; Eibich, Peter (JAI Press, 2025)
A well-documented trend in family demography is that young adults from disadvantaged backgrounds tend to enter their first partnership earlier and forego marriage more often than their advantaged counterparts. Yet, limited research has explored whether there is also an association between parental background and expectations for partnership formation, which are considered important precursors of behaviours. Further, few studies have explored the potential mechanisms mediating these differences. This paper uses data from the British Household Panel Survey and Understanding Society to analyse the relationships between parental socioeconomic status and young Britons' expectations for marriage, cohabitation, and attitudes towards ideal age at marriage. Using the KHB decomposition as a mediation method, we verify whether these relationships are explained by two mechanisms measured during the young adults’ adolescence: family structure socialisation and academic socialisation. We find that marriage expectations are socially stratified in the UK. Those from the least advantaged backgrounds have significantly lower expectations for marriage than the most advantaged, but this difference does not hold for cohabitation. Those from the least advantaged backgrounds are also more uncertain about their ideal age at marriage. Academic socialisation mediates these relationships to a limited extent. Family structure socialisation mediates a greater percentage, especially living with a single parent, rather than married parents, during adolescence.